AlN/CrN multilayer structures with increased thermal stability. (15th March 2017) - Liu, Shiyu; Yang, Yi; Ji, Rong; Zeng, X.T.; Clegg, W.J.
Abstract: CrAlYN nanolayered coatings of greatly enhanced thermal stability have been developed by doping with levels of Y up to 9 at.%. This prevented the complete dissolution of the layered structure after annealing at 1100 °C in Ar for 1 h, commonly observed in coatings with little or no Y content, although the bilayer period increased from ~ 5 nm to ~ 10 nm. The improved thermal stability is attributed to the formation of a continuous YN layer between the CrN and AlN layers, reducing the rate of interdiffusion. Graphical abstract: